Parameter estimation based fault detection and isolation in Wiener and Hammerstein systems - Janczak, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
Fault detection and isolation in Wiener and Hammerstein systems via generation and processing of residual sequences is considered. We assume that some models of the unfaulty Wiener and Hammerstein systems under consideration are known. For Wiener systems, we also assume that their static nonlinear subsystems are invertible.
Keywords: fault detection; fault isolation; parameter estimation; neural networks; nonlinear systems